Analysis of the Relevance of Syafaq Ahmar To Determining the End of Maghrib Prayer Time from the Perspective of Astrology - Zainal, Addiessa Amalia Zainal; Latuconsina, Mahyuddin; Akmal, Muhammad (HISABUNA: Jurnal Ilmu Falak, 2023)
This study aims 1) to determine the beginning and end of the Maghrib prayer time, 2) to determine the criteria for the appearance of Syafaq Ahmar, 3) to determine the relevance of Syafaq Ahmar to the end of the Maghrib prayer time from the perspective of astronomy. This type of research is a qualitative research that is library research "Library Research" with a syar’i and Astronomical approach. The results of this study Maghrib prayer starts from sunset until the disappearance of the red mega or syafaq ahmar. Syafaq Ahmar phenomenon is a natural phenomenon caused by the rotation of the earth which produces light on the western horizon, just before sunset. meanwhile according to astronomy, syafaq ahmar is the influence of the position of the sun setting on the western horizon which becomes a transitional phase from day to night, its appearance is due to the refraction of sunlight by the earth’s atmosphere. From various literatures as well as the views of scholars and astronomers, it is said that Syafaq Ahmar is a reference for the end of the time for the evening prayer and the start of the time for the evening prayer, this is what then makes Syafaq Ahmar inseparable from one of the ways to find out when the time for the evening prayer ends as well as the start of evening time’